Sexual preference : its development in men and women - Bell, Alan P.; Weinberg, Martin S.; Hammersmith, Sue Kiefer (Bloomington: Indiana University Press, 1981)
"Alan P. Bell; Martin S. Weinberg; Sue Kiefer Hammersmith Fonds Suzan Daniel (FSD)"